THE CHILD CUSTODY STATUS FROM UNREGISTERED MARRIAGE: AN ISLAMIC LAW ON THE BASIS OF CONSTITUTIONAL COURT DECISION - Setiawan, Pratiwi; Haryadi, Wahyu Tris (YURIS: Journal of Court and Justice, 2022)
Unregistered marriages have an impact on the marriage itself and on the children born caused its marriage. Even though every child is sacred born and without a sin. A child cannot choose to be born from which parents, nor they can choose to be born from the marriage of their parents. Therefore, a child must be given the protection of their human rights and other rights by their parents, family and the state.The objectives of this research is to find out the child custody status from unregistered marriage on Islamic law in Indonesia. The method used in this research is juridical-normative approach (positive law). The data collection used was classified based on each title. The result of this research showed that the law of unregistered marriage is the same as the law of legal marriage, as regulated in Article 2 paragraph (1) on Law No. 1/1974 regarding of marriage. However, the status of unregistered marriage is still not recognized by Indonesian law, which has been regulated in Article 2 paragraph (2) on Law No. 1/1974. Otherwise, the children status of parents who have unregistered marriages, their status is still not recognized by Law and their custody rights over their mother and mother's family. However, according to Islamic law, the child custody status remains to their parents.The decision of the Constitutional Court will establish the existence of jurisprudential law to realize legal certainty regarding the legal position of children out of wedlock so that they obtain complete legal protection from their parents.